Adherence to cancer screening guidelines across Canadian provinces: an observational study - Strumpf, Erin C (BioMed Central, 2010)
BACKGROUND: Cancer screening guidelines reflect the costs and benefits of population-based screening based on evidence from clinical trials. While most of the existing literature on compliance with cancer screening guidelines only measures raw screening rates in the target age groups, we used a novel approach to estimate degree of guideline compliance across Canadian provinces for breast, colorectal and prostate cancer screening. Measuring compliance as the change in age-specific screening rates at the guideline-recommended initiation age (50), we generally found screening patterns across Canadian provinces that were not consistent with guideline compliance. METHODS: We calculated age-cancer-specific screening rates for ages 40-60 using the Canadian Community Health Survey (2003 and 2005), a cross-sectional, nationally representative survey of health status, health care utilization and health determinants in the Canadian population. We estimated the degree of compliance using logistic regression to measure the change in adjusted screening rates at the guideline-recommended initiation age for each province in the sample. RESULTS: For breast cancer, after adjusting for age trends and other covariates, being above age 50 in Quebec increased the probability of being screened by 19 percentage points, from an average screening rate of 24% among 40-49 year olds. None of the other regions exhibited a statistically significant change in screening rates at age 50. Additional analyses indicated that these patterns reflect asymptomatic screening and that Quebec's breast cancer screening program enhanced the degree of guideline compliance in that province. Colorectal cancer screening practice was consistent with guidelines only in Saskatchewan, as screening rates increased at age 50 by 12 percentage points, from an average rate of 6% among 40-49 year olds. For prostate cancer, the regions examined here are not compliant with Canadian guidelines since screening rates were quite high, and there was not a discrete increase at any particular age. CONCLUSIONS: Screening practice for breast, colorectal and prostate cancer was generally not consistent with Canadian clinical guidelines. Quebec (breast) and Saskatchewan (colorectal) were exceptions to this, and the impact of Quebec's breast cancer screening program suggests a role for policy in improving screening guideline compliance.